2016
DOI: 10.17756/nwj.2015-014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Multicomponent Nanoparticles for Immobilization of Heavy Metals in Aqueous Phase

Abstract: This study is focused on the preparation of multicomponent nanoparticles (MCNPs) used to remediate artificial and real mine tailings. The nanoparticles were synthesized with 0.035 M or 0.007 M of sodium sulfate, 0.5 M of iron chloride and 0.8 M of sodium borohydride. Characterization of nanoparticles performed with a Transmission Electron Microscope (TEM), X-ray diffractometer (XRD), Fourier Transform Infrared Spectrometer (FTIR), and X-ray Photoelectron Spectrometer (XPS) demonstrated, these materials are in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…This suggests that this sorption system is not a first, second, third, and pseudo-first order reactions and that the pseudo-second order model, based on the assumption that the rate-limiting step could be chemisorption involving valency forces through sharing or exchange of electrons between heavy metal and Technosol, provides the best correlation of the data ( Ho and McKay, 1999 ). Prior studies reported similar behavior for fitting results of adsorption of heavy metals from artificial mine tailings ( Flores et al., 2015 ). Zhou et al., 2013 informed the same adsorption pattern when these authors studied the removal of heavy metal ions dissolved in metallurgical wastewater using sepolite.…”
Section: Discussionmentioning
confidence: 55%
“…This suggests that this sorption system is not a first, second, third, and pseudo-first order reactions and that the pseudo-second order model, based on the assumption that the rate-limiting step could be chemisorption involving valency forces through sharing or exchange of electrons between heavy metal and Technosol, provides the best correlation of the data ( Ho and McKay, 1999 ). Prior studies reported similar behavior for fitting results of adsorption of heavy metals from artificial mine tailings ( Flores et al., 2015 ). Zhou et al., 2013 informed the same adsorption pattern when these authors studied the removal of heavy metal ions dissolved in metallurgical wastewater using sepolite.…”
Section: Discussionmentioning
confidence: 55%